European Heritage, Dialogue and Digital Practices - Galani, Areti; Mason, Rhiannon; Arrigoni, Gabi (Critical Heritages of Europe, 2020)
European Heritage, Dialogue and Digital Practices focuses on the intersection of heritage, dialogue and digital culture in the context of Europe. Responding to the increased emphasis on the potential for heritage and digital technologies to foster dialogue and engender communitarian identities in Europe, the book explores what kind of role digital tools, platforms and practices play in supporting and challenging dialogue about heritage in the region. Drawing on fieldwork involving several European museums and heritage organisations, the chapters in this volume critically engage with the role of digital technology in heritage work and its association with ideas of democratisation, multivocality and possibilities for feedback and dialogic engagement in the emerging digital public sphere. The book also provides a framework for understanding dialogue in relation to other commonly used approaches in heritage institutions, such as participation, engagement and intercultural exchange. The authors map out the complex landscape of digitally mediated heritage practices in Europe, both official and unofficial, by capturing three distinct areas of practice: perceptions and applications of digitally mediated dialogues around heritage within European museums and cultural policy, facilitation of dialogue between European museums and communities through participatory design approaches and non-official mobilisation of heritage on social media.